Addressing the problem of obesity and associated cardiometabolic risk in black South African women - time for action! - Julia H. Goedecke (Taylor & Francis Group, 2017)
The PhD thesis of Gradidge, entitled 'Factors associated with obesity and metabolic syndrome in an ageing cohort of black women living in Soweto, Johannesburg (Study of Women in and Entering Endocrine Transition [SWEET])', attempts to understand the determinants of obesity and metabolic syndrome (MetS) in a population of urban-dwelling black South African women. A conceptual framework is presented, which positions obesity as the central risk factor for MetS, and includes the possible influence of socioeconomic status, lifestyle behaviours and body size perceptions, as key determinants of obesity. This commentary focuses on the two main findings of Gradidge's thesis, namely, (i) physical activity and sedentary behaviour, and (ii) body composition and adiponectin, as risk factors for obesity and MetS in black South African women. Despite a high prevalence of obesity (48%), Gradidge showed that 75% of the women taking part in the study were meeting WHO guidelines on physical activity. This commentary suggests that the relationship between physical activity and cardiometabolic risk may be confounded by socioeconomic status. Alternatively, the intensity, and not necessarily the volume, of activity, as well as high rates of sedentary behaviour are posited as important determinants of obesity and MetS in black South African women. Accordingly, this commentary questions the veracity of the WHO guidelines on physical activity in developing countries, where most women meet the guidelines but have very poor cardiorespiratory fitness, are obese and are at high risk of MetS. Gradidge also showed that the most consistent and significant correlate of MetS in this cohort of middle-aged women was low serum levels of adiponectin. This commentary highlights various lifestyle interventions that have been shown to increase adiponectin levels. Finally, the importance of immediate action to address the problem of obesity and MetS is emphasised.